(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Although education is considered a necessity, more andmore parents are educating their daughters still learning household work for agirl is given importance. They cannot negate house hold work to most of womentheir daughters are helpful in household duties. Katai (1939) study perceivedthat household work was still the responsibility of working women.